UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI PENERAPAN STRATEGI QUIZ TEAM DALAM PEMBELAJARAN KOOPERATIF DI KELAS XI Ak3 SMK MUHAMMADIYAH 2 PEKANBARU - Gusheri Gusheri; Syofni Syofni; Kartini Kartini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
AbstractThis research is classroom action research that aims to improve mathematics learning outcomes by applying Quiz Team strategy in cooperative learning. The subjects were students of class XI Ak3 SMK Muhammadiyah 2 Pekanbaru in the semester of the school year 2013/2014. The number of students in class XI Ak3 are 38 people consist of four boys and 34 girls with heterogeneous levels of academic ability. The research consist of two cycles. Each cycle has four stages, the stages are planning, implementation, observation and reflection. Each end of the cycle done tests. Data collected through observation and achievement tests. Data were analyzed by descriptive narrative analysis and descriptive statistical analysis. Criteria for success of the action is successful if the quality of the learning process increase and number of students who achieve a minimum completeness criteria increase on the tests I and II. The percentage of students who achieve a minimum completeness criteria before action, the tests I and II respective 21.05%, 31.58%, and 57.89%. Percentage achievement of the minimum completeness criteria indicate that the implementation of the strategy Quiz Team in cooperative learning can improve mathematics learning outcomes of students in class XI Ak3 SMK Muhammadiyah 2 Pekanbaru.Key words: Classroom action research, Mathematics learning outcome, Cooperative learning, Quiz Team strategy